Between Faith and Doubt - Hick, J. author. aut Link
X, 176 p.
Keywords: This short book is a lively dialogue between a religious believer and a skeptic. It covers all the main issues including different ideas of God, the good and bad in religion, religious experience and neuroscience, pain and suffering, death and life after death, and includes interesting autobiographical revelations.